2022
DOI: 10.3389/fphar.2022.867477
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicine, Succinum, Ameliorates Cognitive Impairment of Carotid Artery Ligation Rats and Inhibits Apoptosis of HT22 Hippocampal Cells via Regulation of the GSK3β/β-Catenin Pathway

Abstract: Succinum is an organic mineral formed from the resin of ancient coniferous and leguminous plants, which is applied for tranquilizing mood, promoting blood circulation, and removing blood stasis in Chinese medicine. For quite a long time, the modern research of succinum mainly focuses on the study of physical and chemical properties and authenticity identification while few reports on its medicinal mechanism. In current study, we evaluated different solvent extracts of succinum on carotid artery ligation rats m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Another study (2022) (26) has also proposed that the active ingredients in Chinese herbal medicines can im-prove the cognitive function of patients by regulating the apoptosis of hippocampal cell apoptosis. This work also showed that after treatment, the Bcl-2 level was higher in the observation group than the control group, and Bax and Casp3 levels were lower (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Another study (2022) (26) has also proposed that the active ingredients in Chinese herbal medicines can im-prove the cognitive function of patients by regulating the apoptosis of hippocampal cell apoptosis. This work also showed that after treatment, the Bcl-2 level was higher in the observation group than the control group, and Bax and Casp3 levels were lower (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…For further process to identify the bioactive compound of succinum, we confirmed that EtOAc PSF was most similar to the PSE effect among the three fractions ( Supplementary Figures S2A,B ). In recent, isopimarane diterpenes showing anti-inflammation properties have been proposed as a bioactive compound of succinum, and it ameliorated cognitive impairment via inhibiting hippocampal apoptosis ( Tungcharoen et al, 2020 ; Wei et al, 2022 ). As mentioned above, we speculate that terpenes-based compounds may involve with the anti-neuroinflammatory and antidepressant-like effects.…”
Section: Discussionmentioning
confidence: 99%